Negative Prejudice Resistance Of Baby Boomer Generation Toward Social Media Through One Day One Juz Program - Amiruna, Silmi; Mazaya, Vyki (Munazzama: Journal of Islamic Management and Pilgrimage, 2022)
The research approach used is qualitative with primary data sources in the form of informants using direct interviews or using questionnaires through google forms. Then secondary data in the form of important documents regarding the One Day One Juz ROHIS Irhamna program at SMA Negeri 1 Wiradesa, books, manuscripts, and documentation. And the use of the naturalistic inquiry method to obtain research results in the form of resisting the negative prejudices of the baby boomers generation towards social media through the One Day One Juz program at SMA Negeri 1 Wiradesa. The results show that the One Day One Juz program exists to resist the negative prejudices of the baby boomers generation towards social media. The One Day One Juz program was created to answer the use of social media, both for school learning (the world) and the benefits of the hereafter. The program also received a good response from the baby boomers generation because of the use of social media as a place to read the Qur'an together. Moreover, the One Day One Juz program can also resist negative prejudices from the baby boomers generation to the 13th generation in SMA Negeri 1 Wiradesa, which is 57.14%. millennials in surfing on social media.***Pendekatan penelitian yang digunakan adalah kualitatif dengan sumber data primer berupa informan dengan menggunakan wawancara secara langsung maupun menggunakan kuesioner melalui google formulir. Kemudian data sekunder berupa dokumen penting mengenai program One Day One Juz ROHIS Irhamna SMA Negeri 1 Wiradesa, buku-buku, naskah, dan dokumentasi. Serta penggunaan metode naturalistic inquiry untuk mendapatkan hasil penelitian berupa meresistensi prasangka negatif generasi baby boomers terhadap media sosial melalui program One Day One Juz di SMA Negeri 1 Wiradesa. Hasil penelitian menunjukkan bahwa program One Day One Juz ada untuk meresistensi prasangka negatif generasi baby boomers terhadap media sosial. Program One Day One Juz dibuat untuk menjawab pemanfaatan-pemanfaatan media sosial, baik digunakan untuk pembelajaran sekolah (dunia) maupun untuk kepentingan akhirat. Program tersebut juga mendapatkan tanggapan baik dari generasi baby boomers sebab akan pemanfaatan media sosial sebagai ajang untuk membaca Al-Qur'an bersama. Serta program One Day One Juz juga dapat meresistensi prasangka negatif generasi baby boomers hingga generasi 13th generation yang ada di SMA Negeri 1 Wiradesa yaitu sebanyak 57,14% Namun juga tidak bisa dipungkiri prasangka negatif dari generasi baby boomers masih akan tetap bermunculan karena untuk mengontrol generasi milenial dalam berselancar di media sosial.Keywords: Baby boomers, Social Media, One Day One Juz.